Percepções de professoras e gestoras escolares sobre a implementação da BNCC em uma rede de ensino municipal - Vilela, Alessandra Aparecida (2021)
This research proposes to investigate and analyze how teachers and managers in the early years of elementary school in a municipal education network of a city in southern Minas Gerais interpret the implementation of Common National Curriculum Base (BNCC), seeking to understand their perceptions about the implementation of BNCC in the schools of this school network. The studies began with a literature review on the historical facts that influenced the construction of the curriculum as a normative order, with emphasis on the production of authors who discuss public policies such as Saviani and Cury, and other authors who deal with the process of construction of the BNCC with their dilemmas and clashes in our educational scenario, present in the productions of authors who have discussed for some time curricular issues such as Macedo (2014), Cury (2018) and Süssekind (2016). The methodological approach of the research is qualitative in nature, having as data collection procedures the bibliographic research for the constitution of concepts, elaboration and deepening of the theoretical framework, the documentary research in texts that supported the elaboration, implementation and implementation of the BNCC and the Curriculum Reference of Minas Gerais and the online completion questionnaire that was applied to teachers and school. The participants' responses were categorized in the light of Bardin content analysis. The participants were invited to participate voluntarily in the research, and they were presented with the Free and Informed Consent Form (TCLE) that ensures confidentiality in the analysis of the data, according to the guidelines of COEP/UFLA. The perceptions of the study participants show us that the process of implementing the BNCC in the researched municipal education network is in a gradual and flexible development, which impacts on the teaching practice in the form of alignment of this practice with the current curriculum policy, which point to challenges arising from the curriculum policy present in the Base, whether due to adaptation, motivation or even insecurity. We understand that the implementation of the BNCC requires the continuing education of teachers and managers, especially teachers, who are the key elements in the teaching-learning process.